2016
DOI: 10.1098/rspa.2016.0213
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic linear elastic parameter estimation using error in the constitutive equation functional

Abstract: A modified error in the constitutive equation-based approach for identification of heterogeneous and linear anisotropic elastic parameters involving static measurements is proposed and explored. Following an alternating minimization procedure associated with the underlying optimization problem, the new strategy results in an explicit material parameter update formula for general anisotropic material. This immediately allows us to derive the necessary constraints on measured data and thus restrictions on physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…These will further accelerate arterial injury. It is reported that intima changes are very obvious at 4 weeks after radiotherapy, and the changes in media and adventitia begin to appear at 12 weeks after radiotherapy [ 7 ], which is consistent with the present study.…”
Section: Discussionsupporting
confidence: 93%
“…These will further accelerate arterial injury. It is reported that intima changes are very obvious at 4 weeks after radiotherapy, and the changes in media and adventitia begin to appear at 12 weeks after radiotherapy [ 7 ], which is consistent with the present study.…”
Section: Discussionsupporting
confidence: 93%
“…In this case, we have to zero the vertical motion of the top edge in order to neglect the virtual work done by the unknown traction. To establish such type 1 virtual field, we assign a transverse virtual motion on the top edge and solve the incompressible elasticity problem posed by Eqs ( 6) and (7). We can also choose Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Then we find u i * by solving Eqs ( 6) and ( 7) on ωi and by assigning u i * =0 on the boundaries of all inclusions but i  . In the next section, we will compare the performance of conventional virtual fields with the virtual fields satisfying Eqs ( 6) and (7).…”
Section: Type 1: Virtual Fields Obtained From Finite Element Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many dedicated mathematical and computational algorithms for the reconstruction of location and parameters of anomalies of different geometrical nature (cavities, cracks, and inclusions) have been proposed over the past few decades (see, for instance, [1,4,6,12,13,14,15,21,26,27,29,31,33,34,42,43,55], the survey articles [16,11], and the monograph [5]). Most of the classical techniques are suited to continuous measurements, in other words, to experimental setups allowing to measure continuum deformations inside the elastic body or on a substantial part of its boundary.…”
Section: Introductionmentioning
confidence: 99%